Arthralgia and Extraintestinal Manifestations in Crohn’s Disease Elevate the Risk of IBD-Related Arthritis over Sacroiliitis - Ivan Giovannini; Nicola Cabas; Marco Marino; Annarita Tullio; Ilaria Tinazzi; Angela Variola; Carmelo Cicciò; Fabro Cinzia; Berretti Debora; Chiara Zuiani; Rossano Girometti; Luca Quartuccio; et al. (Rheumatology and Therapy)
Abstract Introduction Inflammatory bowel disease (IBD) related arthritis is the most prevalent extraintestinal manifestation (EIM) of IBD, ranging between 10 and 39%. Magnetic resonance enterography (MRE) is used to assess small bowel disease involvement in Crohn’s disease (CD) and can detect signs of sacroiliitis in up to 23.5% of patients. The predicting role of sacroiliitis detected on MRE is still unknown. The aim of this study is to evaluate the predictive role of sacroiliitis at MRE and other clinical features for IBD-related arthritis development in a cohort of adult patients with CD. Methods Between December 2012 and May 2020, consecutive patients with CD who performed MRE were enrolled in the study. Patients with a previous diagnosis of IBD-related arthritis were excluded. A baseline demographics and clinical characteristics of the patients were retrospectively collected. The identification of new-onset IBD-related arthritis events during the follow-up was based on rheumatological clinical diagnosis and fulfillment of the ASAS classification criteria. Results Ninety-five patients, mean age 43.9 years (standard deviation [SD] ± 16.6), 52.6% female were enrolled in the study with a median follow-up of 83 months (Q25:75 25:143). Six out 95 (6.3%) developed IBD-related arthritis with a mean time of 11 months (SD ± 16.8). Sacroiliitis detected on MRE was not associated with an increased risk of IBD-related arthritis (odds ratio [OR] = 2.12 [95% confidence interval (CI) 0.36, 12.53, p = 0.408]). In contrast, the presence of arthralgia and EIMs were found to be a predictor for IBD-related arthritis development (OR = 84.0 [95% CI 8.18, 862.39, p < 0.0001] and OR = 7.37 [95% CI 1.25, 43.32, p = 0.027], respectively). Conclusions This study highlights that sacroiliitis, as assessed by MRE, was not associated with the development of IBD-related arthritis, whereas extraintestinal manifestations and arthralgia were significantly associated with later IBD-related arthritis development in patients with CD.